Short-term Outcome of Plasma Adsorption Therapy in Amyotrophic Lateral Sclerosis: Plasma Adsorption Therapy in Amyotrophic Lateral Sclerosis - Li, Bin; Zhang, Wei; Zhong, Shaoxin; Pan, Jianyi; Wang, Xiaohong; Zou, Hequn; Dou, Xianrui (Journal of Medical Biochemistry, 2022)
Background: To observe the short-term outcome of plasma adsorption（PA）therapy in amyotrophic lateral sclerosis (ALS). Methods: 28 cases of ALS patients were recruited in this study, of which 20 were male and 8 were female with a mean age of 53.21 ±9.07 years and the average course of 33±23.35 months. The clinical manifestations were limb weakness (N=27), muscular atrophy (N=27), muscular tremor (N=5), dysphagia (N=12) and dysarthria (N=12). The clinical data of the patients recruited were graded by Amyotrophic Lateral Sclerosis Functional Rating Scale Revised (ALSFRSR) : <10 (N=1), 11-20 (N=4), 21-30 (N=6), 31-40 (N=12), >40 (N=5). All patients received PA therapy once a week for three successive times after examining the conditions of blood coagulation and virus infection. PA therapy was supplemented with neurotrophic therapy meanwhile. All patients’ clinical manifestations and scores of ALSFRSR before treatment and one week after treatment were evaluated and compared. The levels of serum superoxide dismutase (SOD), interleukin-10 (IL-10), serum creatine kinase (CK) and lactate dehydrogenase (LDH) before and after treatment were compared. Results: After PA therapy, 14 patients have improved obviously in muscle strength, 4 patients in hypermyotonia partially, 3 patients in muscular tremor, 5 patients in dysarthria, 3 patients in salivation to some extent and 2 patients in swallowing function. The score of ALSFRSR after PA treatment (31.89±10.36) was remarkably higher than that before PA treatment (30.68±10.52) (P<0.01). The levels of SOD (155.10±21.87 u/ml) and IL-10 (138.06±185.88 pg/ml) after PA treatment were significantly higher than the levels before PA treatment (143.08.3±19.16 u/ml and 46.34±75.31 pg/ml, respectively) (P<0.05). The levels of CK (168.86±113.50 u/L) and LDH (152.07±32.65 u/L) after PA treatment were significantly lower than the levels before PA treatment (356.68±250.30 u/L and 181.36±33.74 u/L respectively) (P<0.01). At the end of follow-up period (November, 2016), five patients died of respiratory failure 16-21 months after PA treatment and two patents died from respiratory infections 15-20 months after PA treatment. 7 patients were still alive. The scores of ALSFRS-R of these patients were 13.00±13.37, obviously lower than those before PA treatment (36.71±8.56) (P<0.05) and 4 week after PA treatment (38.14±8.82) (P<0.05). Conclusions: Plasma adsorption (PA) therapy has short-term therapeutic effects on ALS. The effects might be attributed to the anti-oxygen free radical effect by increasing SOD level and the anti-inflammation effect by increasing IL-10 level. As the efficacy of PA therapy was obtained in a small sample size and short follow-up period, the long-term observation of PA efficacy in treating ALS should be further investigated.